An analytical model on static smoke exhaust in Atria - Chow, Cheuk Lun; Li, Junmei (Journal of Civil Engineering and Management, 2010)
Static smoke exhaust systems with natural vents are starting to be installed in big shopping complexes, ware‐houses and cargo terminals in the Far East. These systems are used for natural ventilation as well as for letting out smoke. This paper responds to concerns over the performance of static smoke exhaust systems, which remain less popular than dynamic smoke exhaust systems with mechanical fans. We propose a modification of a simple flow model found in the literature, adapting this to study smoke layer interface height with natural vents opened. We compare and justify our results, as generated by both Computational Fluid Dynamics and zone models, alongside reports of historical field tests. The model of smoke exhaust is applied in an illustrative example of a large hall, leading to the suggestion that a flow model could be used for designing natural vents. As the key driving force in removing smoke through natural vents is smoke’s own buoyancy, the system might only be effective for bigger fires. First Published Online: 10 Feb 2011